1991
DOI: 10.1007/bf01314331
|View full text |Cite
|
Sign up to set email alerts
|

Canine distemper virus infection and encephalitis in javelinas (collared peccaries)

Abstract: Canine distemper virus has been isolated in dog lymphocyte cultures from the brains of three javelinas that became moribund with signs of encephalitis. Canine distemper viral antigen was demonstrated predominantly in neurons and morbillivirus-like structures were seen by electron microscopy in brains of diseased animals. Serological studies suggest that CDV infection may be common in javelinas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 12 publications
0
33
1
1
Order By: Relevance
“…The virus has been reported to cause disease in members of the carnivore families of Ailuridae, Felidae, Hyaenidae, Mustelidae, Procyonidae, Ursidae, Viverridae, and Phocidae (12). In addition, CDV has also been reported to infect javelinas (13) and was recently detected in rodents (14). A natural outbreak with CDV in nonhuman primates was first reported in 1989 when 22 Japanese macaques (Macaca fuscata) housed in an animal research facility seroconverted to CDV (15).…”
Section: Anine Distemper Virus (Cdv) Is a Member Of The Familymentioning
confidence: 99%
“…The virus has been reported to cause disease in members of the carnivore families of Ailuridae, Felidae, Hyaenidae, Mustelidae, Procyonidae, Ursidae, Viverridae, and Phocidae (12). In addition, CDV has also been reported to infect javelinas (13) and was recently detected in rodents (14). A natural outbreak with CDV in nonhuman primates was first reported in 1989 when 22 Japanese macaques (Macaca fuscata) housed in an animal research facility seroconverted to CDV (15).…”
Section: Anine Distemper Virus (Cdv) Is a Member Of The Familymentioning
confidence: 99%
“…Together with Measles virus (MV) and Rinderpest virus, it belongs to the morbilliviruses which form a serologically closely related genus in the family Paramyxoviridae. CDV primarily affects dogs, but infections of other terrestrial carnivores, in both captivity and the wild, have been reported (1,2,18,21,22,25,26,29,33,36). The mortality rates associated with CDV infection vary among susceptible species and range from 0% in domestic cats to 50% in dogs and 100% in ferrets.…”
mentioning
confidence: 99%
“…anine distemper virus (CDV) exhibits a number of unique properties compared to other members of the Morbillivirus genus, including its propensity to jump species barriers (4,22) and its ability to spread to the central nervous system (CNS) in a high percentage of infected animals (8). However, different CDV strains display various levels of neurovirulence, induce neurological sequelae at a range of time points, and target different regions of the CNS (41).…”
mentioning
confidence: 99%